Pengukuran Produktivitas dengan Menggunakan Metode Objective Matrix pada Proses Produksi UD. Kopi Teungku Aceh - Edy Fradinata; Bella Marsella; Nur Izzaty (Fakultas Teknik, 2022)
UD. Teungku Aceh Coffee is a business engaged in coffee production. In the November 2020-October 2021 period, this business has not been able to achieve the predetermined production target, which is 300 kg per day and 7,000 kg per month. The purpose of this study was to measure partial productivity in the production process using the Objective Matrix (OMAX) method. The second objective is to provide recommendations for improvement of the ratio that causes a decrease in productivity based on fault tree analysis (FTA). The criteria measured are the use of raw materials, labor hours, production line workers, machine working hours and electrical energy consumption. Based on the results of the OMAX calculation, the lowest ratio score is the ratio 1, which means that it causes a decrease in productivity in the UD production process. Kopi Teungku Aceh is ratio 1. Recommendations for improvement are given to increase productivity in ratio 1, namely, forming an inspection section as a raw material inspection division by making an analysis report (LA) as evidence that raw material inspection has been carried out, making a firewood storage area in the factory yard that is empty, performs a mixed drying process between natural and automatic drying and ensures the availability of suppliers in the timely delivery of raw materials.